The Norwegian Microbiota Study in Anorexia Nervosa (NORMA): Integrating a clinical trial with preclinical experiments–A study protocol - Ida Heir Hovland; Lasse Bang; Anne Mari Herfindal; Stine Sofie Strømland; Tina Bogetvedt Spernes; Armita Jahanshahi; Kathinka Larsen Otterdal; Dunja Arsenovic; Trude Elise Aspholm; Ylva Vik; Jenny H. M. Storvik; Monica Hauger Carlsen; et al. (PLoS ONE, 2026)
Background Anorexia nervosa (AN) remains difficult to treat, partly due to co-occurring mental health challenges and gastrointestinal symptoms. Emerging research suggests that individuals with AN exhibit gut microbiota dysbiosis and dysregulation in the gut-brain axis (GBA). However, research examining the role of gut microbiota as a potential driver of AN-related pathologies remains limited. The Norwegian Microbiota Study in Anorexia Nervosa (NORMA) will therefore investigate gut microbiota and its interaction with the GBA in AN. Methods NORMA is a collaboration between the Norwegian University of Life Sciences and seven Norwegian specialized eating disorder inpatient treatment units, consisting of three work packages (WP): a clinical observational trial (WP1), in vitro fermentation experiments (WP2), and animal experiments (WP3). In WP1, 90 patients with AN (age 16–50, BMI < 18.5) admitted for treatment and 90 healthy controls (HCs, age 16–50, BMI 18.5–27) will be recruited. Data on mental and physical health, dietary intake, and blood and fecal samples for biomarker and microbiota analyses will be collected at baseline, 6 and 12 weeks after start of treatment for AN patients and once for HCs. Outcomes will be compared between groups, and longitudinal effects of standard treatment examined within the AN group. In WP2, fecal microorganisms from patients and HCs will be grown in vitro to assess influence of prebiotics. In WP3, mice will receive fecal microbiota from AN and HC donors to determine if and how AN‑related microbiota affects AN‑relevant phenotypes. Conclusion NORMA is pioneering in its integration of clinical, in vitro, and animal studies, providing the most comprehensive gut microbiota study of AN so far. By investigating the role of gut microbiota in AN and effects of standardized treatment on gut microbiota composition, this study aims to inform the development of innovative therapeutic strategies and ultimately improve treatment outcomes and life quality for individuals with AN. Trial registration NORMA is a registered clinical trial: clinicaltrials.gov as NCT06144905 .